UCA1 involved in the metformin-regulated bladder cancer cell proliferation and glycolysis - Tian Li; Xiangzhou Sun; Xianhan Jiang (Tumor Biology, 2017)
Despite great scientific advances have been achieved in cancer treatment in recent years, the death rate of bladder cancer has been staying at a high level. Metformin, a widely-used and low-cost diabetes medicine, might have the potential of anticancer. The aim of this study was to evaluate the effects of metformin on bladder cancer cells and to identify potential molecular targets and signaling pathways. Bladder cancer 5637 cells transfected with either pcDNA/UCA1 vector or pcDNA3.1 empty vector were treated with various doses of metformin for different periods of time, and then cell proliferation and glycolysis were assessed. Reverse transcription polymerase chain reaction and Western blotting were applied to examine the expression of long non-coding RNA UCA1 and mammalian target of rapamycin–signal transducer and activator of transcription pathway molecules. We found metformin inhibited bladder cancer cell proliferation in a dose- and time-dependent manner. UCA1-overexpressed 5637 cells showed increased proliferation and glycolysis compared with control cells. Metformin downregulated both endogenous and exogenous UCA1 expression, leading to the inhibition of mammalian target of rapamycin–signal transducer and activator of transcription 3–hexokinase 2 signaling pathway. Our study provided the first evidence that metformin inhibited proliferation and glycolysis in cancer cells through regulation of long non-coding RNA UCA1. The discovery also suggested the important roles of long non-coding RNA in chemoprevention, which is a property of metformin.